Economics : A Very Short Introduction - Dasgupta, Partha (Oxford Oxford University Press, 2007)
Combining a global approach with examples from everyday life, this work describes the lives of two children who live very different lives in different parts of the world: in the Mid-West USA and in Ethiopia. Along the way, it provides an introduction to key economic factors and concepts such as individual choices, national policies, and equity.
Include Illustrations, References, Glossary and Index.
A Very Short Introduction.
Keywords: Economics